2005
DOI: 10.1182/blood-2003-07-2367
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-associated CD154 in immune thrombocytopenic purpura

Abstract: Ripoche CD40-ligand (CD154) is expressed on activated CD4 ؉ T lymphocytes and is essential for the T cell-dependent activation of B lymphocytes. CD154 is also expressed at the activated platelet surface. In this study, we show that platelet-associated CD154 is increased in immune thrombocytopenic purpura (ITP), a disease characterized by an autoimmune response against proteins of the platelet membrane. CD154 and its messenger RNA were also present in increased amounts in the megakaryocytes of patients with ITP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 22 publications
2
63
1
3
Order By: Relevance
“…18 Others have shown that human platelets from immune thrombocytopenic purpura patients can directly stimulate autologous B cells to produce antiplatelet antibodies in vitro. 41 In addition to direct stimulation of B cells, platelets, through direct contact with T cells, release RANTES, creating a feedback loop for T-cell response amplification. 42 Furthermore, adoptively transferred human platelets via CD154 have been shown to cause immune-mediated rejection of allografts in mice.…”
Section: Discussionmentioning
confidence: 99%
“…18 Others have shown that human platelets from immune thrombocytopenic purpura patients can directly stimulate autologous B cells to produce antiplatelet antibodies in vitro. 41 In addition to direct stimulation of B cells, platelets, through direct contact with T cells, release RANTES, creating a feedback loop for T-cell response amplification. 42 Furthermore, adoptively transferred human platelets via CD154 have been shown to cause immune-mediated rejection of allografts in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, le CD154 plaquettaire est capable d'activer les cellules dendritiques et d'induire la prolifération des lymphocytes B naïfs [15,31]. Ces données sont renforcées par la démonstration in vivo, dans des modèles murins, du rôle du CD154 plaquettaire dans la réponse immunitaire contre des virus [32].…”
Section: Compétence Immunologique Du Cd154 Plaquettaireunclassified
“…Cette maladie se caractérise par la présence d'auto-anticorps ciblant des déterminants antigé-niques présents sur les plaquettes, essentiellement la glycoprotéine GPIIb/IIIa, et responsables d'une destruction accélérée des plaquettes dans la rate et le foie. La capacité du CD154 plaquettaire à stimuler la prolifération des lymphocytes B et la différenciation des lymphocytes B autoréactifs dans le PTI a permis de suggérer l'implication du CD154 dans le processus d'auto-immunisation [15].…”
Section: Auto-immunitéunclassified
“…a more active role in the autoimmune process than simply bearing antigens and accepting a fate of destruction. 28 A number of investigators have studied the pattern of cytokine production in ITP. While there are conflicting results, most reports favor the interpretation that adult chronic ITP represents a predominantly Th1 type immune response characterized by production of interleukin-2 (IL-2) and interferon-γ (IFNγ).…”
Section: Emergence Of Antiplatelet Antibodiesmentioning
confidence: 99%